Noninvasive Molecular Imaging of the Enhanced Permeability and Retention Effect by (64)Cu-Liposomes: In vivo Correlations with (68)Ga-RGD, Fluid Pressure, Diffusivity and (18)F-FDG - Børresen, Betina (Int J Nanomedicine, 2020)
BACKGROUND: The accumulation of liposome encapsulated chemotherapy in solid cancers is dependent on the presence of the enhanced permeability and retention (EPR) effect. Positron emission tomography (PET) imaging with a liposome encapsulated radioisotope, such as liposome encapsulated Cu-64 ((64)Cu-liposome) may help to identify tumors with high liposome accumulation, and thereby stratify patients based on expected benefit from liposomal chemotherapy. However, intravenous administration of liposomes without a cytotoxic content is complicated by the accelerated blood clearance (ABC) phenomenon for succeeding therapeutic liposome dosing. Alternative markers for assessing the tumor’s EPR level are therefore warranted. MATERIALS AND METHODS: To increase our understanding of EPR variations and to ultimately identify an alternative marker for the EPR effect, we investigated the correlation between (64)Cu-liposome PET/CT (EPR effect) and (68)Ga-RGD PET/CT (neoangiogenesis), (18)F-FDG PET/CT (glycolysis), diffusion-weighted MRI (diffusivity) and interstitial fluid pressure in two experimental cancer models (CT26 and COLO 205). RESULTS: (64)Cu-liposome and (68)Ga-RGD SUV(max) displayed a significant moderate correlation, however, none of the other parameters evaluated displayed significant correlations. These results indicate that differences in neoangiogenesis may explain some EPR variability, however, as correlations were only moderate and not observed for SUV(mean), (68)Ga-RGD is probably insufficient to serve as a stand-alone surrogate marker for quantifying the EPR effect and stratifying patients.